Integrating Education, Technology, and Suistanable Practices for Community Empowerment in Siponjot Village - Zahedi; Dian Marisha Putri; Katrin Jenny Sirait; T. Irmansyah; Dolly Sojuangan Siregar; Miswar Budi Mulya; Benny Hidayat; Muhammadin Hamid; M. Sabri; Badai Charamsar Nusantara; Meutia Nauly (Talenta Publisher, 2025)
This study explores the implementation of a holistic community service program in Siponjot Village, North Sumatra, aimed at enhancing non-formal education, economic sustainability, and environmental resilience. Through the